2010
DOI: 10.1590/s1413-70542010000400022
|View full text |Cite
|
Sign up to set email alerts
|

Influência do potássio e da calagem na composição química, qualidade fisiológica e na atividade enzimática de sementes de soja

Abstract: Ciênc. agrotec., Lavras, v. 34, n. 4, p. 953-960, jul./ago., 2010 RESUMOA composição química das sementes pode ser influenciada por fatores genéticos, ambientais e pela disponibilidade de nutrientes no solo durante a produção e, como consequência, terem o seu vigor afetado. O potássio pode influenciar a atividade de várias enzimas presentes nas plantas, necessárias em várias reações envolvidas na utilização de energia, síntese de amido, metabolismo do nitrogênio e respiração. Avaliou-se o efeito da adubaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
19

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 5 publications
5
33
0
19
Order By: Relevance
“…Similar pattern was observed by VEIGA et al (2010). The only observed difference is related to the presence of a band, of 95kDa molecular weight, in cultivar 'BRS267'.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Similar pattern was observed by VEIGA et al (2010). The only observed difference is related to the presence of a band, of 95kDa molecular weight, in cultivar 'BRS267'.…”
Section: Resultssupporting
confidence: 80%
“…According to MINUZZI et al (2009) the protein content of soybean seeds is heavily influenced by the environment, mainly during the grain filling. Unlikely, VEIGA et al (2010) showed significant reduction in the grain composition as result of increased potassium content.…”
Section: Resultsmentioning
confidence: 69%
“…Studies that relate mineral nutrition and enzyme activity in soybean seeds are scarce. In this regard, Veiga et al (2010) did not observe differences between the activities of MDH as a result of potassium fertilization and liming. *Mean values followed by the same letter in the column do not differ among themselves at 5% probability by the ScottKnott test.…”
Section: Malate Dehydrogenasementioning
confidence: 71%
“…EST is involved in lipid breakdown during the seed germination process. This process is relevant for renewed growth of the embryonic axis, especially in seeds rich in lipids, as is the case of soybeans (Veiga et al, 2010).…”
Section: Results and Discusssion Esterasementioning
confidence: 99%
See 1 more Smart Citation